Actitudes y conocimientos de intensivistas colombianos sobre donación y trasplantes: Retos actuales para el país (2023)
Background. Donation rate and the number of transplants performed in Colombia have decreased. Currently, a new health rule that requests training of health staff in intensive care units to encourage donation, is being implemented. Objective. This study aims to identify Colombian intensive care physicians’ attitudes and knowledge about donation. Materials and methods. This is a cross-sectional, descriptive study performed through a structured questionnaire, sent by e-mail to members of the Colombian Association of Critical Care Medicine. Results. 93.75% of participants would donate organs after death, 97.9% would donate organs from a death family member, 95.83% would donate as living donor to a family member. 88.33% have communicated to their family their intention to donate, 41.66% acknowledge some donation promotional campaigns, 12.5% carry donor card. 22.92% have donated blood during the last year; 66.66% consider that it is important to improve communication of donation strategies between staff members of critical care units; 60.42% don’t talk about donation with families of potential donors; 54.17% don’t know Colombian legislation about donation and transplantation; 18.75% consider fair/poor its working relationship with transplant coordinators; and 43.75% have an unfavorable concept of Colombian transplantation model. Conclusions. Participants show a favorable attitude towards organ donation. However, there is no significant knowledge on Colombian legal issues of donation. Participants do not routinely talk about donation. Resolution 2003 of 2014 will positively influence on national rates of donation given that additionally to intensive care staff training, they have the opportunity to become part of the transplant process and to manage transplant coordination activities. Formation of new transplant coordinators, and integration of intermediate cities to the National Net of Transplant, will also help to increase donation rates. © 2015, Universidad Nacional de Colombia. All rights reserved.